Cold-water coral mounds and reefs off Mauritania and associated megafauna - Hammoud El Vadhel; Hammoud El Vadhel; Lene Buhl-Mortensen; Mohamed El Khalil Med Mahmoud; Yeslem El Vally; Beyah Meissa; François Le Loc’h; Lenaick Menot (Frontiers in Marine Science, 2025)
This study presents the megafauna related to coral mounds (coral remains) and cold-water coral (CWC) reefs off Mauritania. The mound-specific megafauna was documented by comparing 47 trawl catches from coral mounds with 47 catches from off-mound areas, sampled from 1982 to 2022. Coral reef megafauna were described from eleven ROV dives conducted during two surveys held in 2020 and 2021. The mound and reef environment were documented using data from 2159 CTD profiles collected between 1995 and 2022. A detailed annotation of the ROV recorded videos was undertaken, and megafauna habitat relations were identified using multivariate statistics. The coral ecosystems that supported a rich megafauna were situated in the oxygen minimum zone at depths of 400 to 650 meters, with an average temperature of 10.55°C. The coral mound hosted 31% more species than adjacent off-mound areas, and fish contributed 66% of the taxa of five groups, followed by crustaceans contributing with 20%. The five most common species were Helicolenus dactylopterus, Laemonema laureysi, Merluccius polli, Malacocephalus occidentalis and Hoplostethus cadenati. The CWC reefs hosted 120 taxa representing 11 different faunal groups, with fish as the most species rich group, contributing 39% of the recorded taxa, followed by cnidarians represented by several corals (18 taxa) and crustaceans (17 taxa). The most abundant taxa on the reefs, in addition to the reef-building coral Desmophyllum pertusum, were the anemone Synarachnactis cf. lloydii, the corals Acanthogorgia cf. hirsuta and Swiftia phaeton, the crustaceans Nematocarcinus africanus and Eumunida bella, the fish H. dactylopterus, the bivalve Acesta excavata and the sponge Cladorhiza corallophila. Live coral, sand and mud were environmental drivers of species distribution on the reefs, and separate communities were related to different reef habitats. This study provides the first comprehensive description of the megafauna related to the cold-water coral mounds and reefs off Mauritania. The rich megafauna associated with these ecosystems highlights the urgent need for conservation measures, particularly in light of increasing pressures from oil and gas activities, deep-sea fishing, and the impact of climate change.